Exposure to green-blue spaces and mental health: a retrospective e-cohort study in Wales. (November 2021) - Thompson, Daniel A; Fry, Richard; Watkins, Alan; Mizen, Amy; Akbari, Ashley; Garrett, Joanne; Geary, Rebecca; Lovell, Rebecca; Lyons, Ronan A; Nieuwenhuijsen, Mark; Rowney, Francis; Stratton, Gareth; et al.
Abstract: Background: Growing cross-sectional evidence links access to green-blue spaces with mental health benefits, but studies at an individual level and at a national population scale are scarce. This gap can be addressed through the Secure Anonymised Information Linkage (SAIL) Databank, which allows household-level green-blue spaces access and exposure data to be linked to individual-level health-care use. Methods: Within the SAIL Databank, an e-cohort of the population of Wales (2008–19) was created from green-blue space metrics and the Welsh Longitudinal General Practice database. Green-blue spaces metrics (derived from satellite imagery and planning data) included average ambient greenness within 300 m of the home (designated as the Enhanced Vegetation Index) and average access to green-blue spaces (designated as the number of green-blue spaces within 1600 m of the home). A validated algorithm was applied to create a common mental health disorder flag and linked to green-blue spaces exposure (ambient greenness and access) recorded for individuals not affected by common mental health disorders. We used multivariate logistic regression models to test the hypothesis that greater green-blue spaces exposure is associated with a reduced likelihood of a flagged common mental health disorder. Subgroup analyses were done for socioeconomic deprivation. Findings: The e-cohort comprised 2 341 591 individuals (1 193 240 men and 1 148 351 women), aged 16 or over and registered with a general practice in the SAIL Databank. After adjusting for individual and area-level covariates, a unit increase in ambient greenness around the home and access to green-blue spaces within 1600 m were associated with lower odds of a common mental health disorder (adjusted odds ratio 0·11 [95% CI 0·11–0·12] for ambient greenness around the home and 0·47 [0·46–0·48] for access to green-blue spaces within 1600 m). A unit increase in ambient greenness was associated with reduced odds of a common mental health disorder for residents of the most deprived areas (n=473 410; 0·22 [0·20–0·24]) and of the least deprived areas (n=480 424; 0·07 [0·07–0·08]). Interpretation: People with greater exposure to green-blue spaces were less likely to develop a common mental health disorder and the effect is modified by socioeconomic deprivation. This finding has implications for both public health policy and urban planning. This large, adult-population cohort provides sufficient power to examine variations between subgroups to investigate inequalities. Funding: The project was developed as part of independent research funded by the National Institute for Health Research (study number 16/07/07).